(3TLQI Gdchfs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdCMOj GdPGJ GdaQOj GdUaGJ GdPj JbOS hLgg Yf GdLgGJ hbOSI Yf GdeMOKGJ hbOeg Yf GdLgGJ s
(3BNQgG (B:s
(3UdGI JMd HgG YbOJj hMSHfG Gddg hfYe Gdhcjd hdGMhd hdGbhI EdG HGddg GdYdi GdYXje hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde hGdMeO ddg QH GdYGdejf JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3hbO ocJHJ HBdg cGJHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B41s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdeYGQa GdYGeIs